Development of Children’s Religiousity in Dual Career Family - Iswati Iswati (Jurusan PGMI FTIK IAIN Metro Lampung, 2019)
This study aimed to describe the development of children's religious life from a family of dual career families, namely families where both father and mother both work outside the home and undergo certain professions. How is the parenting style and pattern of education applied by parents to keep the child's awareness and religious attitudes in good condition, and what factors are the supporters and inhibitors of the development of a child's religious spirit in the dual career family ?. Child restrictions referred to in this study are children in the range of primary school age, namely between the ages of 7-11 years. Based on data collected from 6 families of working mothers' fathers who are respondents, the results of the study show that families generally realize that parents are still the first and foremost place for child growth and development, so that the main function of the family is not to be educated, caring, socializing children so that children can carry out their functions in society properly, remains a top priority. Parenting that is applied in the family is generally appropriate, namely democratic parenting and education patterns as a place to socialize the ideal second child, namely the school environment that has an orientation on spiritual development in addition to academic orientation. While the supporting and inhibiting factors of the process of developing mindfulness in children are generally influenced by the internal and external factors of children, the school environment, the community and most importantly parents.